1992
DOI: 10.1096/fasebj.6.3.1740232
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gastric mucosal injury: laboratory models reveal mechanisms of pathogenesis and new therapeutic strategies

Abstract: Gastric ulcer is a multifaceted, pluricausal illness. Knowledge of the pathophysiology of gastric ulcer disease remains incomplete. Current pharmacological management of gastric ulceration is directed primarily at the reduction or neutralization of gastric acid secretion despite evidence that patients with this disease often exhibit normal gastric secretory activity. Attempts have been made to prevent or reduce gastric mucosal injury by cytoprotective agents without diminishing gastric acidity. We review sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
11

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(130 citation statements)
references
References 36 publications
3
116
0
11
Order By: Relevance
“…The ethanol-induced gastric ulcer experimental model is a simple and reproducible procedure and, therefore, may be considered a test of choice for screening samples with possible antiulcerogenic effects. 52,53 The gastroprotective activity of A. chica extract in ethanol-induced ulcer formation in rats was previously reported by Jorge,54 employing 100 mg⋅kg , and 300 mg⋅kg dose was sufficient to reduce 58% of the ULI in comparison to the control group (saline) ( Figure 6, Figure S2). …”
Section: Antiulcerogenic Activitysupporting
confidence: 62%
“…The ethanol-induced gastric ulcer experimental model is a simple and reproducible procedure and, therefore, may be considered a test of choice for screening samples with possible antiulcerogenic effects. 52,53 The gastroprotective activity of A. chica extract in ethanol-induced ulcer formation in rats was previously reported by Jorge,54 employing 100 mg⋅kg , and 300 mg⋅kg dose was sufficient to reduce 58% of the ULI in comparison to the control group (saline) ( Figure 6, Figure S2). …”
Section: Antiulcerogenic Activitysupporting
confidence: 62%
“…Ethanol, a common ulcerogen, produces severe haemorrhagic erosions in the glandular (mucosal) part of the stomach (Ezike et al, 2009) from mechanisms such as direct toxic action, reduction of the secretion of bicarbonate, depletion of gastric wall mucus (Al-Harbi et al, 1997), stimulation of the synthesis and release of leukotriene C 4 (Peskar et al, 1986) and significant production of oxygen free radicals which increase lipid peroxidation and damage cells (Pihan et al, 1987). It also reduces endogenous glutathione and prostaglandin levels and increases the release of histamine, influx of calcium ions and generation of free radicals (Galvin and Szabo, 1992). Thus, the action of the extract and fractions in this model suggests cytoprotective action possibly mediated through enhancement of mucosal defensive factors.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 h the rats orally received 0.5 mL of ethanol (PA-Synth) via a stainless steel intubation needle to induce gastric ulcers (Glavin & Szabo, 1992;Mota et al, 2008). The animals were euthanized 1 h after treatment with the ulcerogenic agent.…”
Section: Ethanol-induced Gastric Lesionsmentioning
confidence: 99%
“…Two different models of the production of peptic ulcers (ethanol and indomethacin) (Hayden et al, 1978;Glavin & Szabo, 1992) were used, with the intention of checking the traditional use of latex. The results using the gastric lesion model induced by the oral administration of ethanol demonstrated that the formation of ulcerations and petechiae were induced in different percentages in the mucous of the stomach.…”
Section: Controlmentioning
confidence: 99%